Effectiveness of pelvic floor muscles strengthening exercises in the prevention of urinary incontinence: a systematic review (Research, Society and Development, 2022)
Objective: to identify the effective interventions performed to strengthen the pelvic floor muscles and their effects on urinary incontinence. Method: a systematic review, with a temporal delimitation of 25 years, carried out between January 2019 and October 2021, using the Medical Literature Analysis and Retrieval System Online, SCOPUS, Cochrane and Latin American and Caribbean Literature on Health Sciences databases, in Portuguese, English or Spanish. Results: 14 articles were included, originating from research carried out in Brazil, USA, Norway, Australia and Iran. Most interventions were within the physiotherapeutic aspect, electrostimulation and kinesiotherapy. Conclusion: interventions such as kinesiotherapy and electrical stimulation act as positive agents in strengthening the pelvic floor muscles. Health education can significantly contribute to raising this awareness.